2000
DOI: 10.1038/sj.cdd.4400740
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial cytochrome c levels and mitochondrial hyperpolarization precede camptothecin-induced apoptosis in Jurkat cells

Abstract: Mitochondria play a central role in apoptosis through release of cytochrome c and activation of caspases. In the present study, we showed that, in Jurkat human T cells, camptothecininduced apoptosis is preceded by (i) an increase in cytochrome c and subunit IV of cytochrome c oxidase (COX IV) levels in mitochondria; and (ii) an elevation of the mitochondrial membrane potential (DC m ). These events are followed by cytochrome c release into the cytosol, cytochrome c and COX IV depletion from mitochondria, exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
99
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 37 publications
15
99
1
1
Order By: Relevance
“…Transient MHP is an early event preceding caspase activation, phosphatidylserine (PS) externalization, and disruption of Δψ m in Fas- [6] and H 2 O 2 -induced apoptosis of Jurkat human leukemia T cells and normal human peripheral blood lymphocytes (PBL) [8]. These observations were widely confirmed and extended to other apoptosis pathways [9,10,11,12,13,14]. Transient MHP is also triggered by activation of T cells by Con A [6] and CD3/CD28 costimulation [15] via ROI-and Ca 2+ -dependent production of NO [16].…”
Section: Introductionmentioning
confidence: 84%
“…Transient MHP is an early event preceding caspase activation, phosphatidylserine (PS) externalization, and disruption of Δψ m in Fas- [6] and H 2 O 2 -induced apoptosis of Jurkat human leukemia T cells and normal human peripheral blood lymphocytes (PBL) [8]. These observations were widely confirmed and extended to other apoptosis pathways [9,10,11,12,13,14]. Transient MHP is also triggered by activation of T cells by Con A [6] and CD3/CD28 costimulation [15] via ROI-and Ca 2+ -dependent production of NO [16].…”
Section: Introductionmentioning
confidence: 84%
“…This result is reminiscent of those of other investigators, who concluded that an early increase in Dc m is a common event in the process of apoptosis in a variety of cells with different proapoptotic stimuli including CPT. [33][34][35] We have shown that mitochondrial hyperpolarization in leishmanial cells is prevented by treatment with oligomycin prior to the treatment with CPT. From this result it is confirmed that F 0 -F 1 ATPase-like protein in leishmanial cells plays a very important role in the increase of mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…In drug-induced apoptosis, accumulating evidence shows that cytochrome c release from mitochondria into the cytosol is an early event preceeding the activation of caspases (Sanchez-Alcazar et al, 2000). In contrast, in most cells, Fas and other death receptors directly activate caspases-8 and -3 via a mitochondria-independent pathway.…”
Section: Npm-alk Decreases Cytochrome C Release Into the Cytosol Of Dmentioning
confidence: 99%